2005
DOI: 10.2135/cropsci2005.0305
|View full text |Cite
|
Sign up to set email alerts
|

Pasture and Stocker Cattle Performance on Furrow-Irrigated Alfalfa and Tall Wheatgrass Pastures, Southern High Plains, USA

Abstract: Alfalfa (Medicago sativa L.) and tall wheatgrass [Agropyron elongatum (Host) Beauv., = Elytrigia elongata (Host) Nevski] monocultures and mixtures were rotationally and continuously grazed by beef stockers (Bos taurus L.) in the 1999 to 2001 growing seasons. Pastures sown with 5.1 kg pure live seed (PLS) ha−1 alfalfa and 13.5 kg PLS ha−1 tall wheatgrass produced regrowth containing approximately 60% alfalfa, while postgrazing herbage mass was approximately 50% alfalfa. No differences (P < 0.05) were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 18 publications
2
19
0
1
Order By: Relevance
“…In this study, LUC young bulls had a remarkable performance compared with the data of other works conducted with steers that grazed on lucerne with (Perry et al, 1971) or without grain supplementation (Schlegel et al, 2000;Lauriault et al, 2005). This may partly be explained by the different diets, breeds and sexual status of animals in the current and aforementioned studies.…”
Section: Discussionsupporting
confidence: 46%
“…In this study, LUC young bulls had a remarkable performance compared with the data of other works conducted with steers that grazed on lucerne with (Perry et al, 1971) or without grain supplementation (Schlegel et al, 2000;Lauriault et al, 2005). This may partly be explained by the different diets, breeds and sexual status of animals in the current and aforementioned studies.…”
Section: Discussionsupporting
confidence: 46%
“…Wedin et al (1965) found that when the legume proportion of mixed swards [predominantly smooth bromegrass ( Bromus inermis L.)–alfalfa] fell below 20%, total mixture yield was less than grass + 157 kg N ha −1 yr −1 When 45 kg N ha −1 yr −1 was applied to legume depleted stands, animal performance was similar to grass + N with additional benefit gained by applying 157 kg N ha −1 yr −1 to similar stands in which the legume component was <20% (Wedin et al, 1965). The difference between the results reported here, in which no nitrogen was applied to pastures having <20% legume component and those of Wedin et al (1965) might be related to the difference between established legumes in a stabilized community (Lauriault et al, 2003) and a new seeding, in which the legumes winterkilled before the community became stabilized (Wedin et al, 1965). Harris et al (1999) stated that the legume proportion of New Zealand white clover–perennial ryegrass dairy pastures equilibrated at 15% and that it was difficult to develop and maintain higher proportions.…”
Section: Resultsmentioning
confidence: 99%
“…All legumes have limitations (Leep et al, 2002), so it is likely that only one or two species can maximize productivity in a given environment (Beuselinck et al, 1994; Skinner et al, 2004), especially in productive sites (Harmoney et al, 2001) under grazing (Leep et al, 2002). Even when more complex pastures mixtures are sown, the number of persistent species often declines within a few seasons (Skinner et al, 2004; Tracy and Sanderson, 2004b; Wedin et al, 1965). Alfalfa has been the legume of choice in most of the USA (Haynes, 1980), but bloat is a concern in addition to stand longevity (Guldan et al, 2000; Lauriault et al, 2005a; Rumburg, 1978).…”
mentioning
confidence: 99%
“…and rye [Secale cereale L.]). Alternatively, Lauriault et al (2005) reported ADG of 0.94 kg hd −1 d −1 for steers grazing alfalfa and TW pasture in Tucumcari, NM, that was flood irrigated at 800 mm season −1 . Mean of five forage nutritive value measures for each pasture replicate for grass-only and grass-legume treatment systems for 2 yr in Lubbock, TX.…”
Section: Animal Responsesmentioning
confidence: 99%
“…This greater gain was the result of a longer grazing season (185 d on average) and late-season CP supplementation. Lauriault et al (2005) reported 1539 kg total LWG for steers grazing alfalfa and TW pasture for 140 d. Total LWG for steers in the grass-legume treatment was 576, 894, and 908 kg LWG ha −1 for 86, 115, and 113 grazing days, respectively. Steers rotationally grazing in low-water-input grass systems gained 43 to 122 kg LWG ha −1 , whereas those on moderate-waterinput systems gained 381 to 520 kg LWG ha −1 .…”
Section: Animal Responsesmentioning
confidence: 99%